Development and experimental validation of high performance embedded intelligence and fail-operational urban surround perception solutions of the PRYSTINE project - Novickis Rihards; Levinskis Aleksandrs; Fescenko Vitalijs; Kadikis Roberts; Ozols Kaspars; Ryabokon Anna; Schorn Rupert; Koszescha Jochen; Solmaz Selim; Stettinger Georg; Adu-Kyere Akwasi; Halla-Aho Lauri; et al. (MDPI, 2025)
Automated Driving Systems (ADSs) commend a substantial reduction of human-caused road accidents while simultaneously lowering emissions, mitigating congestion, decreasing energy consumption and increasing overall productivity. However, achieving higher SAE levels of driving automation and complying with ISO26262 C and D Automotive Safety Integrity Levels (ASILs) is a multi-disciplinary challenge that requires insights into safety-critical architectures, multi-modal perception and real-time control. This paper presents an assorted effort carried out in the European H2020 ECSEL project—PRYSTINE. In this paper, we (1) investigate Simplex, 1oo2d and hybrid fail-operational computing architectures, (2) devise a multi-modal perception system with fail-safety mechanisms, (3) present a passenger vehicle-based demonstrator for low-speed autonomy and (4) suggest a trust-based fusion approach validated on a heavy-duty truck.